Recovery of integrated and surface trace DNA from illicit drug tablets. (November 2022) - Griffin, Amy; Kirkbride, K. Paul; Henry, Julianne; Painter, Ben; Linacre, Adrian
Abstract: In many parts of the world, tablets are a commonly encountered form of illicit drug preparation. Whilst previous research has investigated the feasibility of detecting trace DNA on illicit drug capsules, this has not been performed for tablets. Tablets have a unique substrate surface and therefore the amount of DNA transferring to them and persisting on them may be different to capsules; there may also be differences in the collection efficiency and the outcome of downstream DNA processing and analysis steps. The ability to profile the DNA from individuals who handled tablets during their preparation and distribution would add another level of discrimination between various drug seizures or corroborate chemical profiling outcomes which may link various seizures to a common origin. DNA from two different individuals (male and female) was added to the tablets in two stages. Firstly, tablet powder was spiked with DNA from one individual to mimic the situation where DNA traces are incorporated during the drug synthesis or final drying stages. The powder was then pressed into tablets in a clean environment without intentional addition of DNA. Subsequently, a second individual counted out the tablets into bags of ten to mimic the preparation for distribution at a user level. The exterior of the tablet was swabbed and then the entire tablet and the swab were put through separate DNA extractions, yielding two DNA extracts for each tablet. Swabs of the exterior tablet surface yielded single source DNA profiles that identified the tablet handler in 100 % of samples. The tablet extract yielded the donor of the DNA intentionally added within the drug powder in 80% of samples with varying levels of support, however contributions of the exterior handler were detected in 60 % of samples. The identification of individuals potentially involved in the synthesis of the drugs compared to the distribution of the tablets will provide invaluable strategic intelligence related to illicit drug investigations and to law enforcement agencies. Graphical Abstract: ga1 Highlights: Trace DNA from two different individuals added within and on tablet. Mimics where one person synthesised the drug and another distributed the tablets. Interior and exterior of tablets sampled giving two DNA extracts per tablet. LR values generated for known donors in respective extracts. Method of separating and detecting DNA from surface and within tablet.